2016
DOI: 10.4081/ejtm.2016.6033
|View full text |Cite
|
Sign up to set email alerts
|

α-linolenic acid reduces TNF-induced apoptosis in C2C12 myoblasts by regulating expression of apoptotic proteins

Abstract: Impaired regeneration and consequent muscle wasting is a major feature of muscle degenerative diseases. Nutritional interventions such as adjuvant strategy for preventing these conditions are recently gaining increasing attention. Ingestion of n3-polyunsaturated fatty acids has been suggested as having a positive impact on muscle diseases. We recently demonstrated that a diet enriched with plant derived n3-fatty acid, α-linolenic acid (ALA), exerts potent beneficial effects in preserving skeletal muscle regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Moreover, a recent study shows that Dox induces apoptosis in rat soleus muscle [ 20 , 21 ]. Data from another recent study shows that TNF- α -induced apoptosis in C2C12 myoblast cells involves a decrease in the BCL2 to BAX ratio, which is consistent with our data [ 37 ]. The current study corroborates the previously published muscle studies on Dox-induced muscle apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a recent study shows that Dox induces apoptosis in rat soleus muscle [ 20 , 21 ]. Data from another recent study shows that TNF- α -induced apoptosis in C2C12 myoblast cells involves a decrease in the BCL2 to BAX ratio, which is consistent with our data [ 37 ]. The current study corroborates the previously published muscle studies on Dox-induced muscle apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…A vacuum was constantly applied to stretch the membrane by 6%, in order to increase membrane stiffness, a condition that preliminary experiments showed to be necessary to allow a proper differentiation of the C2C12 cells into myotubes (data not shown). The following day, at 80% confluence, GM (DMEM with 15% FBS, 4.5 g/L of glucose, 2 mM of L-glutamine, 100 μg/mL of penicillin-streptomycin; Sigma-Aldrich, St. Louis, MO, United States) was replaced with DM containing 2% Horse Serum (HS, Carotenuto et al, 2016). A mixed culture of myoblasts and myotubes was kept for 4 days in DM at 37°C, 5% of CO2 in the Flexcell apparatus, always under constant stretch.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have shown that cachexia is characterized by increased inflammatory markers in the skeletal muscle and by satellite cell activation [18,19]. However, in cachexia satellite cells fail to fuse with muscle fibers and their impairment contributes to muscle wasting [20][21][22]. Recently, Cui and al.…”
Section: Introductionmentioning
confidence: 99%